Competences development and organisational commitment : mediation through employability and moderation by generation - Moreira, Ana (2018)
The main objective of this study is to test the mediating effect of perceived internal employability on the relationship between organisational practices of competences development and affective commitment, and also to test the moderating effect of different generations in this mediation. The sample has 302 participants, who are employees in several organisations based in Portuguese territory. We verified the mediating effect of the employability perception in the relationship between organisational practices of competences development (individualised support and functional rotation) and affective commitment. Regarding the moderating effect of the generations, this effect was verified in the relationship between the organisational competences development practices and the affective commitment in the liaison between the organisational practices of competences development and the perception of internal employability and in the connection between the perception of internal employability and affective commitment.